Knowledge, attitudes and behaviour regarding nutrition and dietary intake of seventh-grade students in rural areas of Mi Yun County, Beijing, China - Wang, Dongxu (Springer Japan, 2013)
OBJECTIVES: To investigate the knowledge, attitudes and behaviour of seventh-grade students regarding nutrition and dietary intake, to collect data that would facilitate the design and implementation of interventions aimed at promoting good nutrition in adolescents via the school and to contribute to the improvement of adolescents’ health in rural regions. METHODS: This was a descriptive, cross-sectional study in which a 27-item, self-administered, structured questionnaire, designed in Chinese, was administered to seventh-grade students attending one of three rural middle schools, chosen randomly from 15 middle schools, in Mi Yun County, Beijing. RESULTS: In terms of nutrition knowledge, 84.5 % of respondents had scores of between 3 and 7. Based on our analysis of the completed questionnaires, during the 7 days preceding completion of the questionnaire 43.6 % of respondents had eaten fresh fruit at least once per day, 71.3 % had eaten vegetables at least once per day, 22.3 % had consumed at least one glass of milk (or soy milk or yogurt) each day and 68.6 % had eaten breakfast every day. In total, 95.2 % of respondents thought nutrition was very important or important to their health, and 94.2 % thought it was very important or important to develop healthy dietary habits. Of the respondents, 52.7 % thought good food quality was the most important aspect of nutrition and dietary intake and 62.2 % thought food safety was the most important aspect. CONCLUSIONS: Based on the results of our survey we suggest their should be continuous efforts to teach adolescents in rural areas of China about various aspects of good nutrition, to encourage diversity in their choice of breakfasts, to guarantee food safety and to improve food quality.